Pengaruh Atribut Perusahaan terhadap Relevansi Laba dan Arus Kas - Gunawan, Barbara; Mirantiningsih, Atika (Journal of Accounting and Investment, 2015)
The purpose of this study is to test whether there are linear or non linear relationship between stock returns with earnings and cash flows in Indonesia, test whether there are non linear explaining stocks returns and how firm-specific attributes such as size, debt level and firm-cycle influence the relative relevance of earnings and cash flows in explaining stock returns. This study using manufacture companies listed in Jakarta Stock Exchanges from periods of 2001 until 2004. This result supports a linear relationship between stock returns with earnings and cash flows. This result non linear can additional information explaining stocks returns. The results based on size, debt level and firm-cycle influence the relative relevance of earnings and cash flows in explaining stock returns. Earnings give additional information for small firms, low leverage firms and growth firms. Cash flows give additional information in explaining stock returns for large firms, debt level high and mature firms.